MULTIMODAL POSTER KAMPANYE ANTIROKOK STIVORO DALAM UPAYA MENGURANGI PREVALENSI MEROKOK DI BELANDA - Andjani, Aurellia Virgie; Sutanarihesti, Triaswarin (Multikultura, 2025)
This study examines the multimodal elements in the campaigns of STIVORO (Stichting Volksgezondheid en Roken), the Netherlands' first national organization dedicated specifically to tobacco control. The objective of this research is to analyze and describe the roles of visual and verbal elements in STIVORO’s campaigns in conveying anti-smoking messages to the Dutch public. This research adopts a qualitative descriptive approach and applies the theory of multimodality developed by Kress and van Leeuwen (2006). The research objects consist of eight posters, classified based on their target audience: active smokers and passive smokers. The findings reveal that visual and verbal elements work collaboratively in constructing anti-smoking messages. However, the modality in the posters targeting active smokers is higher than that in those targeting passive smokers. This is due to the use of real human figures and a more varied color scale in the former group. Moreover, the campaigns aimed at active smokers employ the word Ik (“I”) to establish a more personal connection with the audience, in contrast to the more socially oriented verbal texts found in the posters targeting passive smokers.